"A-OK": Chest Radiograph during Primary Survey Facilitates Faster, More Accurate Endotracheal Tube Position in Injured Children. Issue 5 (May 2019) - Doud, Andrea N.; Gaffley, Michaela; Hostetter, Olivia; Talton, Jennifer W.; Petty, John K.
The Advanced Trauma Life Support algorithm recommends bedside confirmatory techniques to confirm correct endotracheal tube (ETT) depth, a critical component in the care of pediatric trauma patients. We hypothesized that bedside confirmatory techniques are inaccurate and that early chest X-ray (CXR) would overcome such inaccuracies, allowing for faster intervention of malpositioned ETTs. An "A-OK" algorithm of immediate CXR following intubation in injured children aged <16 years was implemented. Eligible patients the years before and after implementation were identified. The accuracy of bedside confirmatory techniques (use of length-based depths and auscultation of breath sounds) was assessed. Post-"A-OK" patients were compared with pre-"A-OK" controls regarding the speed of malpositioned ETTrepositioning. Twenty-eight post-"A-OK" cases and 23 pre-"A-OK" controls were identified. The groups did not differ in baseline characteristics. Bedside confirmatory techniques were accurate in only 61 per cent (length-based depth) and 58 per cent (auscultation of breath sounds) of patients. Time to ETT repositioning was significantly longer in pre-"A-OK" controls than in post-"A-OK" cases (35.2 ± 15.9 minutes vs 21.1 ± 11.8 minutes, P = 0.03). Bedside confirmatory techniques to determine ETT positioning are inaccurate in children. Inclusion of CXR in the primary survey is safe and allows for more rapid repositioning of malpositioned ETTs.